SISTEM INFORMASI ADMINISTRASI KEGIATAN ORGANISASI MAHASISWA (STUDI KASUS: UNIVERSITAS MUHAMMADIYAH CIREBON) (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2022)
The development of information technology is now so advanced, anyone who follows the development of the world of information will find it too fast to be adjusted to the growth of the organization. In line with the development of information technology, many things can make it easier to complete a job. The purpose of this study is to identify and overcome problems that arise from the performance of the current system. Therefore, the Student Affairs Sector requires a system so that there are no errors in processing and storing data. In the process of organizing activities such as submitting activity funds and accountability reports, student organizations must carry out a procedure that has been applied by the student affairs department of the Muhammadiyah University of Cirebon. The problem that occurs at this time is in terms of submitting funds and accountability reports for student organization activities currently still using manual files. The application made is a web-based administrative information system for student organization activities. The website is made using the PHP programming language, as the database is MySQL and the system built is web-based. The final result of this research is the production of an administrative information system for student organization activities at the Muhammadiyah University of Cirebon, so that it can facilitate student organizations in terms of submitting funds, reporting responsibility for activities and facilitating the student department in validating funding applications. Keywords: Information System, Student Organization, PHP and MySQL